Detection of in vivo production of tumour necrosis factor-alpha by human thyroid epithelial cells. - Zheng, R Q (1992)
We have established previously that human thyroid epithelial cells (TEC) from patients with autoimmune thyroiditis are able to synthesize cytokines, such as interleukin-1 (IL-1) and interleukin-6 (IL-6). This paper examines TEC in sections from autoimmune thyroiditis for the in vivo production of tumour necrosis factor-alpha (TNF-alpha) and interferon-gamma (IFN-gamma) using the combined techniques of in situ hybridization and immunohistochemistry. Thyroid tissue from patients with Graves' disease, Hashimoto's disease and non-toxic goitre was examined and both mRNA and the protein of TNF-alpha were detected in TEC on frozen sections. Representative figures of only Graves' samples are illustrated in this paper. In contrast, using the same methods, IFN-gamma was detected only in the infiltrating cells and not in TEC of thyroid tissue from the patients.